EAST EUROPEAN PLATFORM DEVELOPMENT IN THE LATE PRECAMBRIAN AND PALEOZOIC: STRUCTURE AND SEDIMENTATION - Grachev A.F.; Nikolaev V.A.; Nikolaev V.G. (My University, 2006)
In spite of significant quantity of publications, devoted to different aspects of the East European (Russian) platform geology, the joint analysis of structure and sedimentation evolution has not been made. The paper deals with this subject and contains the most recent data. Litho-paleogeographic sketches of the East European platform are examined at different stages. Relations of major lithological complexes, mean rates of sedimentation, and areas covered by sea in Paleozoic and Mesozoic are revealed. The sketches representing structures of the East European platform sedimentary cover in the end of Riphean, in the end of Devonian, and in the end of Permian made it possible to distinguish major boundaries between reconstructions in structural plans. The role of inversion processes in separated local areas is underlined. The main structure of the Russian platform cover has been created during Riphean, Vendian to Early and Middle Paleozoic, and Late Paleozoic stages. The tendency in decreasing of the tectonic activity since Riphean through Mesozoic to Cenozoic takes shape.
Keywords: TECTONICS; STRUCTURAL GEOLOGY; GEODYNAMICS; SEDIMENTOLOGY; EAST EUROPEAN PLATFORM; Палеозой::Пермская; Палеозой::Девонская; Докембрий::Протерозой::Рифей; Докембрий::Протерозой::Неопротерозойская::Вендский; Paleozoic::Permian; Paleozoic::Devonian; Precambrian::Proterozoic::Riphean; Precambrian::Proterozoic::Neoproterozoic::Vendian